Digital method comparision for discrimination of neutrons and gamma-rays with scintillation detector - Phan , Van Chuan; Nguyen , Duc Hoa; Nguyen , Xuan Hai; Nguyen , Ngoc Anh; Pham , Dinh Khang; Dinh , Tien Hung (Nuclear Science and Technology, 2016)
The interference of gamma in neutron spectra reduces the accuracy of measurement results, especially when using the scintillation detector. The digital method can be used to identify either neutron or gamma pulses. In order to select the algorithm for NE213 scintillation detector, the Matlab Simulink tool was used to simulate neutron counting system. The results show that the figure of merits (FOM) of:rise-time discrimination method (RTD), pulsed gradient analysis (PGA) method, charge comparison method (CCM), and correlation pattern method (CPM) are 1.09, 0.66, 2.21 and 1.97, respectively.